2018
DOI: 10.2109/jcersj2.17174
|View full text |Cite
|
Sign up to set email alerts
|

Photo-induced hydrophilicity of brookite TiO<sub>2</sub> prepared by hydrothermal conversion from Mg<sub>2</sub>TiO<sub>4</sub>

Abstract: Super-hydrophilic titanium dioxide (TiO 2 ) photocatalysts with some mild oxidizing ability are favorable for the self-cleaning applications on plastic films. In this study, we have focused on brookite TiO 2 for such purposes. Brookite TiO 2 powders were synthesized by the hydrothermal conversion method using Mg 2 TiO 4 as a precursor. Mg 2 TiO 4 (1 g) and 1 M HCl (30 mL) were put into a polytetrafluoroethylene (PTFE)-lined autoclave. The hydrothermal conversion was conducted at 110150°C for 24 h. The photocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2018
2018
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 25 publications
0
7
0
2
Order By: Relevance
“…In our previous study [8], we reported that the excessive oxidizing ability of anatase TiO 2 caused some problems in the self-cleaning; it formed CaSO 4 white precipitates on a window from atmospheric pollutants. Hence, in our recent study [9], we have focused on brookite TiO 2 with a mild oxidizing ability, which is suitable for the self-cleaning.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study [8], we reported that the excessive oxidizing ability of anatase TiO 2 caused some problems in the self-cleaning; it formed CaSO 4 white precipitates on a window from atmospheric pollutants. Hence, in our recent study [9], we have focused on brookite TiO 2 with a mild oxidizing ability, which is suitable for the self-cleaning.…”
Section: Introductionmentioning
confidence: 99%
“…It is practical to obtain brookite TiO 2 powder, but its phase purity is not as prominent as the Tomita method [13]. In our recent work on the self-cleaning [9], we have synthesized brookite powders via the Kozawa method. Actually, the obtained TiO 2 was a mixture of brookite and rutile, and the highest purity of brookite was 97.2 wt % [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As propriedades auto-limpantes do dióxido de titânio têm sido amplamente pesquisadas por diversos segmentos industriais 53,54 , principalmente em tecnologias de recobrimento em vidros de janelas e em tecidos 55 . Outros estudos abordam seu caráter super-hidrofílico, isto é, superfície polar capaz de absorver a água, ou super-hidrofóbico, que repele a água 56 .…”
Section: Caracterização Dos Filmes De Tio 2 E S-unclassified
“…A formação de filmes finos pode ser dividida em duas classes . As técnicas magnetron sputtering, método hidrotérmico, solvotérmico, e oxidação por micro-arco também têm sido utilizadas 15,17,53,56 . Na Fig.…”
Section: Métodos De Síntese De Filmes De Tiounclassified